A Substractive Clustering Based Fuzzy Hybrid Reference Control Design for Transient Response Improvement of PID Controller - Joelianto, Endra; Sitanggang, Parlindungan H. (Journal of Engineering and Technological Sciences, 2009)
The  well  known  PID  controller  has  inherent  limitations  in  fulfilling simultaneously the conflicting control design objectives.  Parameters of the tuned PID  controller  should  trade  off  the  requirement  of  tracking  set-point performances,  disturbance  rejection  and  stability  robustness.  Combination  of hybrid  reference  control  (HRC)  with  PID  controller  results  in  the  transient response  performances can be independently achieved without deteriorating the disturbance  rejection  properties  and  the  stability  robustness  requirement.  This paper proposes a fuzzy based HRC where the membership functions of the fuzzy logic  system  are  obtained  by  using  a  substractive  clustering  technique.  The proposed  method  guarantees  the  transient  response  performances  satisfaction while preserving the stability robustness of the closed loop system controlled by the  PID  controller  with  effective  and  systematic  procedures  in  designing  the fuzzy hybrid reference control system.